Improving Vocabulary Mastery Javanese Of Ib Class Through Index Card Match Model - Diana Peggy Putinella (ZAHRA: Research and Tought Elementary School of Islam Journal, 2021)
Most of the class IB students have difficulty in using and understanding Javanese vocabulary because students are not accustomed to using Javanese in their daily life. This Classroom Action Research aims to describe the increase in Javanese vocabulary mastery of class IB students at SD Negeri Jetis I for the 2018/2019 academic year through the Index Card Match learning model. Collecting data using the instrument of teacher and student activity observation sheets and student learning outcomes tests. The results of this study indicate that the increase in the average value of the first cycle class is 65 and the second cycle is 77 and the achievement of the Minimum Completeness Criteria (KKM) for the first cycle the average value is 54% and for the second cycle the average value is 75%. Through the Index Card Match learning model, students carry out more focused activities, students' attention becomes more focused on learning objects, students more fluently answer the meaning of vocabulary from Javanese to Indonesian or vice versa.